The clock - Spilsbury, Richard 1963-; Spilsbury, Louise (Chicago, Ill Heinemann, 2012)
Introduces the clock and the history of telling time, from sundials and water clocks to the extremely accurate atomic clocks of today
History of telling time -- Early time technology -- The first mechanical clocks -- Portable clocks -- Electric clocks -- Into the future
The world around us (invention)
Includes bibliographical references (p. 31) and index
1 2 13 15
Keywords: Clocks and watches -- Juvenile literature